2008
DOI: 10.1111/j.1551-2916.2008.02279.x
|View full text |Cite
|
Sign up to set email alerts
|

New MAX‐Phase Compounds in the V–Cr–Al–C System

Abstract: New layered compounds, (V0.5Cr0.5)3AlC2, (V0.5Cr0.5)4AlC3, and (V0.5Cr0.5)5Al2C3 were synthesized by reactive hot pressing V, Cr, Al, and graphite powders. The crystal structures of these new phases were determined using a combination of X‐ray diffraction and scanning transmission electron microscopy. (V0.5Cr0.5)3AlC2 is isotypical to Ti3AlC2; while (V0.5Cr0.5)4AlC3 has the Ti4AlN3 or α‐Ta4AlC3‐type crystal structure. (V0.5Cr0.5)5Al2C3 is formed by periodically stacking of half‐unit cells of (V0.5Cr0.5)2AlC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 27 publications
1
89
0
Order By: Relevance
“…and Hu et al [251,252]), Nb 4 AlC 3 (discovered by Hu et al [241]), the solid solution (V,Cr) 4 [47] have been reported.…”
Section: Ion Bombardment Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…and Hu et al [251,252]), Nb 4 AlC 3 (discovered by Hu et al [241]), the solid solution (V,Cr) 4 [47] have been reported.…”
Section: Ion Bombardment Effectsmentioning
confidence: 99%
“…Zhou et al [47] recently reported a 523 phase, (V,Cr) 5 Al 2 C 3 , as a minority phase in bulk samples consisting primarily of (V,Cr) 2 AlC and (V,Cr) 3 AlC 2 . Figure 5, reproduced from Ref.…”
Section: Intergrown Structures -Hybrid "523" and "725" Max Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid solution space is particularly interesting, as solid solutions often provide improved mechanical properties over their end members 9,34,35 and in some cases are stable even when neither end member is. 36 The ability to accurately determine phase stability from first-principles calculations hinges largely on our ability to identify the most stable competing phases for each composition. Hand-selecting these phases without error from experimental phase diagrams requires meticulous and time-consuming analysis that is only feasible for a small number of compounds at a time.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [12] later reported another "523" phase, (V,Cr) 5 Al 2 C 3 . These compounds have only been observed as minority phases in samples consisting primarily of M 2 AC and M 3 AC 2 (for "523" phases) or M 3 AC 2 and M 4 AC 3 (for "725" phases).…”
mentioning
confidence: 99%